Le territoire comme lieu privilegie de transmission des savoirs et des valeurs des femmes Atikamekw - Basile, Suzy; Asselin, Hugo; Martin, Thibault (Recherches Feministes, 2017)
L’analyse thématique de 32 entrevues réalisées avec des femmes Atikamekw révèle qu’elles connaissent le mode de vie de leurs ancêtres et le rôle que les femmes y jouaient, que ce rôle était prédominant et essentiel dans l’organisation spatiale des activités traditionnelles sur le territoire, que les accouchements sont des marqueurs spatiotemporels, que la désignation du lieu d’origine a changé à la suite des bouleversements sociaux et territoriaux, que la désignation des personnes par le nom traditionnel est toujours en usage, que les femmes Atikamekw étaient responsables de l’éducation. L’obligation d’envoyer les enfants dans les pensionnats de 1955 à 1972 a provoqué une cassure dans la transmission des savoirs sur le territoire et les différentes formes de colonisation ont érodé peu à peu l’influence des femmes.
Keywords: amériques; approches et analyses; canada; care; corps; cours; féminisme autochtone; histoire et politique; intersectionnalité; justice reproductive; justice sociale; maternité; nation Atikamekw; pensionnats; pol4105; premier cycle; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; transmissions; violences; éducation

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires